Cutaneous silent period modulation by tooth clenching, tonic and phasic limb movements in healthy subjects - Kiziltan, Meral E; Gündüz, Aysegül; Hatice Kumru; Tanriverdi, Uygur (Experimental brain research, 2022)
Objective We aimed to examine the modulation of the cutaneous silent period (CSP) by tooth clenching and contralateral tonic dorsiflexion of lower limb and phasic voluntary movements of upper limb. Methods In 18 healthy subjects, we recorded CSP on right thenar muscle after painful stimulation of index finger during mild contraction at six conditions: baseline, maximum tooth clenching, contralateral tonic dorsiflexion of foot, as well as at the beginning (RT1), in the middle (RT2) and at last part (RT3) of the contralateral phasic wrist extension. We measured latency and duration and calculated suppression indices. Results During tooth clenching, the suppression index of second inhibitory phase (I2) was significantly higher than that at baseline condition. The suppression index of first inhibitory phase (I1) was reduced in tonic dorsiflexion. The I2 durations in RT2 and RT3 were longer than that at baseline. The I2 suppression indices during RT1, RT2, and RT3 were significantly higher than that at baseline condition ( p < 0.05). Conclusion The tooth clenching has an inhibitory effect on CSP. The contralateral phasic hand movements caused higher suppression index. The CSP is modulated by remote influences differently depending on the type of muscle contraction (tonic vs. phasic) and/or where it is realized (tooth, upper or lower limb).